2012
DOI: 10.9753/icce.v33.waves.58
|View full text |Cite
|
Sign up to set email alerts
|

Vortical VLF Motions Under Shore-Normal Incident Waves

Abstract: Field observations and numerical model simulations are examined to investigate the magnitude of vortical very low frequency (VLF) velocity fluctuations (i.e. large scale surfzone eddies) under different offshore wave forcing. Observations of vortical VLF motions under shore -normal wave incidence at Duck, NC, USA are re-analyzed and compared with the characteristics of the incident wave spectrum. Long wave periods and narrow frequency spread incident waves were found to coincide with stronger vortical VLF moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…If we define our VLF (very low frequency) band for the periods between 5 and 100 min, the EKE contained in the VLF explains about 70% of the total EKE. The modeled intrinsic EKE in the VLF band is quantitatively comparable to that of the rotational VLFs observed on the same beach [e.g., MacMahan et al ., ; de Schipper et al ., ], clarifying that bathymetric variability is the main source of the intrinsic VLFs. In addition, the VFLs due to group waves [e.g., Long and Özkan‐Haller , ] and individual breaking waves [e.g., Spydell and Feddersen , ], both of which are neglected in the present model, are anticipated to further excite the forced VLFs.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…If we define our VLF (very low frequency) band for the periods between 5 and 100 min, the EKE contained in the VLF explains about 70% of the total EKE. The modeled intrinsic EKE in the VLF band is quantitatively comparable to that of the rotational VLFs observed on the same beach [e.g., MacMahan et al ., ; de Schipper et al ., ], clarifying that bathymetric variability is the main source of the intrinsic VLFs. In addition, the VFLs due to group waves [e.g., Long and Özkan‐Haller , ] and individual breaking waves [e.g., Spydell and Feddersen , ], both of which are neglected in the present model, are anticipated to further excite the forced VLFs.…”
Section: Discussionsupporting
confidence: 65%
“…A quantitatively similar result was reported by de Schipper et al . [], who extended the analysis of MacMahan et al . [] for the much longer period between August and December 1997.…”
Section: Intrinsic Vlfs In 3‐d Transient Rip Currentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although σ L = σ E can be assumed, the dependence of σ on incident wave conditions is not well understood. However, recent research has indicated that for weak alongshore currents, σ E is related to the offshore significant wave height [ MacMahan et al ., ] and period [ de Schipper et al ., ]. For stronger V , surfzone σ E is related to V [ Noyes et al ., ].…”
Section: Discussionmentioning
confidence: 99%